First report of Trichopoda pictipennis (Diptera, Tachinidae) for the Canary Islands - Pablo Caloca; Daniel Suárez; Gustavo Peña; Carlos Ruiz (Biodiversity Data Journal)
The genus Trichopoda Berthold, 1827 is distributed in the Neotropical and Nearctic Regions and some species are very important for biological control. During the last decades, the species Trichopoda pictipennis Bigot, 1876 has received much attention. It is of Neotropical origin, but it has been introduced throughout the western Palaearctic, probably through exchanges that transported its main host, the 'southern green stink bug' Nezara viridula.Trichopoda pictipennis is reported for the first time from the Canary Islands. To date, this introduced species has been detected throughout the island of Tenerife and in a single locality on the island of La Gomera. This finding confirms that this species of Neotropical origin is expanding its range across the Palaearctic realm of this species of Neotropical origin. Parasitised Nezara viridula were collected and reared under laboratory conditions to document the complete life cycle of T. pictipennis. Its potential effects on its main host, as well as on the Canary fauna, are discussed.